AB0302 Bone texture parameters measured at the hand as predictors of outcome in rheumatoid arthritis. (23rd January 2014) - Sparsa, L.; Kolta, S.; Geusens, P.; Briot, K.; Roux, C.
Abstract : Background: Bone and cartilage loss and destruction is associated with rheumatoid arthritis (RA) and inflammation. There is a need for tools for prediction of potential severe patients with poor outcome. The BMA device (D3A™ Medical Systems, Orleans, France) is a high resolution X-ray technique, used to image bone and joints, and to measure bone texture parameters including the fractal dimension (Hmean). Objectives: The aims of this study were to evaluate, by BMA analysis, the metacarpal bone texture in a cohort of 165 RA patients with 1 year follow up, and to assess this new parameter according to the activity of RA. Methods: 165 patients with RA according to ACR criteria were included. They were assessed every 6 months over 1 year, in the context of a prospective study conducted in Maastricht. For this substudy, activity of the disease was assessed by erythrocyte sedimentation rate (ESR), C reactive protein (CRP) and Disease Activity Score (DAS 28) performed at each visit. The bone texture parameters were evaluated on the second and third metacarpal heads of the left hand (MCP2 and MCP3) using BMA device, with standard acquisition at baseline, 6 and 12 months. A single investigator performed all the analyses, with standardized position of regions of interest in the bones. The calculated parameter was Hmean as an approach to bone roughness. Results: We included 57 men and 108 women, mean age 63.63 years [33-89]. The mean disease duration was 9.67 years [2-36]. Among the 138 cases where rheumatoid factor results were available, 75 were positive and among the 11 cases where anti CCP antibodies were available only 6 were positive. Fifty five patients had erosions on X rays of the hands. The mean DAS28 score was 3.34 [0.63-7.35]. Twenty four patients were receiving bisphosphonate during the study. Hmean was similar in MCP2 and MCP3 at baseline: 0.411±0.038 and 0.412±0.043 respectively; H mean MCP2 was correlated with disease duration (-0.17, p=0.03). There was an increase in H mean MCP2 (+ 1.0% p=0.0004) over 1 year. ESR and CRP were correlated with H mean MCP3 at baseline (-0, 15, p=0.055; -0.15 p=0.06) and 6 months (-0.22 p=0.006, -0.25 p=0.002 respectively). DAS was correlated with H mean MCP3 at 6 months (-0.14, p=0.07) and H mean MCP2 at 12 months (-0.16 p=0.04). Conclusions: This new high resolution digital X-ray device provides bone texture parameters of metacarpal heads in RA patients. This preliminary analysis suggests that these parameters measured at the metacarpal heads are influenced by disease duration and activity. Disclosure of Interest: None Declared